Cultural Clash: Investigating How Entrepreneural Characteristics and Culture Diffusion affect International Interns’ Competency - Ligia, Emila; Iskandar, Kurniawaty; Surajaya, I Ketut; Bayasut, Mahir; Jayanagara, Oscar; Mizuno, Kosuke (Aptisi Transactions On Technopreneurship (ATT), 2024)
The world today is highly interconnected. To address the manpower shortage in Japan and the surplus in Indonesia 30 years ago, both countries developed an internship program, "Ginou Jisshu." During the internship, participants with Indonesian culture-based individual characteristics are exposed to Japanese work culture. This study aimed to investigate how interns' individual characteristics and their assimilation of Japanese work culture improve their competency and competitiveness, considering self-efficacy as a moderating factor. Using a quantitative research method, data from 400 internship alumni across 38 provinces in Indonesia were collected through Google Form questionnaires and analyzed using PLS-SEM. Out of 10 proposed hypotheses, all direct effect hypotheses were accepted, and 3 of the moderation hypotheses were accepted, while 2 were rejected. This study introduces a novel paradigm where any positive effect, regardless of statistical significance, is considered beneficial. It suggests that resolving issues, even minor ones, can amplify positive effects and mitigate negative effects. The findings reveal that individual characteristics and Japanese work culture positively affect competency and competitiveness, and competency further enhances competitiveness. Self-efficacy strengthens the impact of individual characteristics and Japanese work culture on competency, as well as the impact of Japanese work culture and competency on individual competitiveness. However, it weakens the effect of individual characteristics and competency on individual competitiveness.